Complete Recovery Following Intestine Perforation Caused by Tuberculosis: A Case Report - Budi, Ikhsan; Fakhrury, Rey Mas; Lupita, Nahdah; Nurusshofa, Zahra (Ahmar Metastasis Health Journal, 2026)
Intestinal tuberculosis (ITB) can mimic common gastrointestinal disorders and is frequently diagnosed late, particularly in resource-limited settings where microbiological confirmation is unavailable. This case report aims to describe an unusual presentation of ITB as ileocaecal perforation and to highlight diagnostic and therapeutic considerations. The method used was a descriptive case report of a 25-year-old woman who presented with watery diarrhoea, vomiting, diffuse abdominal pain, fever, weight loss, and cough, and subsequently developed generalized peritonitis requiring emergency exploratory laparotomy. Intraoperative findings revealed an ileocaecal perforation requiring segmental resection with primary anastomosis. Histopathological examination of the resected bowel and regional lymph nodes demonstrated necrotising granulomatous inflammation with caseation and Langhans-type giant cells, supporting the diagnosis of ITB. Microbiological tests such as GeneXpert and culture were not performed due to resource limitations. Postoperatively, the patient received supportive care, antibiotics, and standard anti-tuberculosis therapy. The results showed a favorable clinical outcome, with no early postoperative complications, discharge on postoperative day seven, and complete symptom resolution with weight gain and radiological improvement at follow-up. This case illustrates that when microbiological confirmation is not feasible, histopathology combined with timely surgical intervention and anti-tuberculosis therapy can support diagnosis and lead to successful management of complicated ITB.